2008
DOI: 10.1007/s00384-008-0576-z
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant crypt foci: endoscopic assessment and cell kinetics characterization

Abstract: Background and aims Aberrant crypt foci (ACF) are preneoplastic lesions in animal models of colorectal cancer. The aim of the study is to investigate if ACF are involved in human colorectal carcinogenic process and if they can be helpful in predicting the presence of a colorectal neoplasia. Methods The study included, between 2003 and 2005, 182 patients, 62 with adenoma, 55 with colorectal carcinoma, 53 without colorectal lesions, and 12 with nonneoplastic mucosal polyps. The number of rectal ACF was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…Indeed, some articles found a decreased apoptosis ratio (27) and others an increase (28). Moreover, several works strongly support the hypothesis that microadenomas are the earliest identifiable lesions in the adenoma-carcinoma sequence in humans because of their resistance to apoptosis, which can lead to a selective growth advantage and a transformed morphology (28,29). Turning the apoptotic machinery on and off is determined by the ratio of proapoptotic and antiapoptotic proteins.…”
Section: Apoptosis In Microadenomasmentioning
confidence: 90%
“…Indeed, some articles found a decreased apoptosis ratio (27) and others an increase (28). Moreover, several works strongly support the hypothesis that microadenomas are the earliest identifiable lesions in the adenoma-carcinoma sequence in humans because of their resistance to apoptosis, which can lead to a selective growth advantage and a transformed morphology (28,29). Turning the apoptotic machinery on and off is determined by the ratio of proapoptotic and antiapoptotic proteins.…”
Section: Apoptosis In Microadenomasmentioning
confidence: 90%
“…In our study, solid tumors in the colon of DMH-challenged rats were not observed and changes were confined to the presence of inflammatory foci and the sporadic early pre-neoplastic lesions, typical for the development of colon cancer. The crypt cavitation in lymphoid tissues is one of the early pathological changes that could lead to the formation of adenoma in the presence of persisting uncontrolled inflammation [23]. Administration of DMH caused significant increase of CTMC numbers and decrease of the number of goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical, epidemiological and biological evidences support the role of ACF in human colorectal tumourigenesis as a putative precursor to colorectal adenomas [7] even if their fast yearly turnover indicates the dynamic nature of the process, and impairs their use as a clinical intermediate biomarker [8].…”
Section: From Aberrant Crypts Towards Adenomamentioning
confidence: 97%